Efektywność badań statutowych i własnych w uczelniach publicznych w 2005 r. - Pasewicz, Wiesław; Świtłyk, Michał (The Effectiveness of Statutory and Own Research in Public Universities in 2005, 2009)
The aim of this study was to determine the effectiveness of expenditure of funds for financing own and statutory research in public universities in 2005 with the use of the DEA method and to determine the effectiveness ranking of universities. The sample included 52 public universities. CRS technical efficiency coefficients and the test group VRS were in 0.749 and 0.889. Proposed amendments to the 2005 rate effects related to increased resources for statutory and own research were included. Optimal solution proposals include reducing the total employment of 19,793 persons
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 216-223